2013
DOI: 10.14712/23362936.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Metronidazole and X-ray Induced Cytotoxicity and Oxidative Stress in Male Germ Cells in Mice

Abstract: Metronidazole (MTZ) is a common antiparasitic and antibacterial drug. The drug and X-ray induced effects in mouse sperm count, sperm head abnormality and some oxidative stress parameters have been studied. Simultaneously the protective role of curcumin has been evaluated. MTZ, 40 mg/kg bw and 13.4 mg/kg bw × 3 days exposure induced abnormal sperm head and reduced total sperm count in Swiss albino mice both after 24 h and 35 days of exposure. However, MTZ treatment in mice receiving X-ray irradiation (0.5 Gy) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Hydrogen peroxide is further deactivated by catalase (CAT) or glutathione peroxidases (GSH-Px) to water and oxygen. Numerous studies reported that curcumin (8 mg/kg) [ 108 ], EGCG (100 mg/kg) [ 109 ], or quercetin ( 0.027% in the diet) [ 110 ] reversed oxidative stress-caused reduction of GSH and SOD levels in mice or rats. Resveratrol protects against oxidative damage by increasing expressions of SOD1, CAT, and heme oxygenase-1 (HO-1) as well as the activity of SOD [ 111 , 112 ].…”
Section: Potential Anti-aging Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide is further deactivated by catalase (CAT) or glutathione peroxidases (GSH-Px) to water and oxygen. Numerous studies reported that curcumin (8 mg/kg) [ 108 ], EGCG (100 mg/kg) [ 109 ], or quercetin ( 0.027% in the diet) [ 110 ] reversed oxidative stress-caused reduction of GSH and SOD levels in mice or rats. Resveratrol protects against oxidative damage by increasing expressions of SOD1, CAT, and heme oxygenase-1 (HO-1) as well as the activity of SOD [ 111 , 112 ].…”
Section: Potential Anti-aging Mechanismsmentioning
confidence: 99%
“…Therefore, as shown in Figure 1 , polyphenols may protect cells from oxidative stress by multiple mechanisms. Indeed, it was shown that curcumin could directly scavenge ROS [ 127 ], increase the expression of endogenous antioxidants [ 108 ], activate the Nrf2 pathway [ 119 ], and modulate miRNAs [ 128 ].…”
Section: Potential Anti-aging Mechanismsmentioning
confidence: 99%
“…This effect was associated with the reduction in oxidative stress, lipid peroxidation and decreased accumulation of dialdehydes as a result of the modulation of various stress-responsive genes [ 279 ]. According to studies, the dietary intake of curcumin (2 mg/g medium) enhanced SOD activity by 32% in Drosophila , while the administration of curcumin (8 mg/kg, intraperitoneal injection for 5 days) to mice was able to restore X-ray-reduced hepatic SOD and GSH contents [ 280 , 281 ]. Curcumin not only upregulates the sirtuin pathway but also activates the Nrf2-ARE pathway [ 282 ].…”
Section: Impact Of Natural Compounds On Cvd Riskmentioning
confidence: 99%
“…Dietary intake of curcumin (2-mg/g medium) increased SOD activity by (32% in Drosophila [70]. In mice, curcumin treatment (8 mg/kg, ip injection for 5 days) can restore X-ray-reduced hepatic SOD and GSH contents [116]. Similarly, resveratrol (50 μM) [117], EGCG (100 mg/kg, intradermal injection) [118] or quercetin (0.027% in the diet) [119] reversed oxidative stress-caused reduction of GSH and SOD levels in mice or rats.…”
Section: Anti Aging Mechanisms Of Phytochemicalsmentioning
confidence: 99%